Absence of TFE3 Immunoexpression in a Spectrum of Cutaneous Mixed Tumors: A Retrospective Pilot Study - Hatice B. Zengin; Bahadir Yildiz; Tatsiana Pukhalskaya; Bruce R. Smoller (MDPI AG, 2022)
Background: Cutaneous mixed tumors (CMTs) include benign, atypical, and malignant chondroid syringomas. This spectrum of entities is known to be a part of myoepithelial neoplasms, which display considerable genetic heterogeneity. In a previous report, a malignant chondroid syringoma (MCS) demonstrated PHF1-TFE3 gene fusion and strong TFE3 immunohistochemical (IHC) staining. The authors suggested that the MCS is genetically related to tumors with TFE3 rearrangements such as renal cell carcinoma and might have genetic heterogeneity. In this study, we aim to investigate potential TFE3 gene fusions with TFE3 IHC stain in a spectrum of CMTs. Materials: Eleven benign chondroid syringoma (BCS), one atypical chondroid syringoma (ACS), and one malignant chondroid syringoma cases were identified, stained with TFE3 IHC stain, and interpreted based on preset criteria. Results: ACS and MCS cases did not show any staining. In 7 of 11 BCS cases, weak (1+) staining was observed in less than 20% of the tumor cells and were considered negative. Additionally, in one BCS case, weak (1+) and (2+) staining was shown in approximately 15% and less than 1% of the tumor cells, respectively. Based on our positivity criteria, this case was also interpreted as negative. Conclusions: Our study failed to reveal possible TFE3 gene fusion by IHC staining in benign, atypical, and malignant chondroid syringomas. Although the negative staining in MCS suggests a genetic heterogeneity in this entity, further studies with larger case groups are needed for a more definitive conclusion.